Preparation of nano-hydroxyapatite/chitosan aqueous dispersions: from lab scale to continuous production using an innovative static mixer - Ruphuy, Gabriela (2018)
Chitosan is widely used in the preparation of organic-inorganic composite materials, such as n-HAp/CS composites, which ﬁndapplication for bone regeneration. The methods for their preparation are various, and usually based on the preparation of intermediate n-HAp/CS dispersions, which can greatly inﬂuence the ﬁnal properties of the resulting composites since it is expected that homogenous and stable dispersions lead to composite materials with improved ﬁnal properties. This work hypothesizes that, additionally to process parameters such as pH, n-HAp/CS weight ratio, mixing conditions and the presence of salts, chitosan itself has a high impact on dispersions stability. Thus, the importance of properly control the preparation of the n-HAp/CS intermediate dispersions is highlighted by doing a systematic study where relevant processing parameters were studied at lab scale using ultrasonication, alone or in the presence of chitosan, namely on particle size and zeta potential. Furthermore, and based on the best laboratorial conditions, the production of n-HAp/CS nanocomposite dispersions in continuous mode was attempted through NETmix® technology,an innovative static mixer and reactor developed at the Associate Laboratory LSRE-LCM of the Faculty of Engineering of the University of Porto(FEUP).